2004
DOI: 10.1046/j.1540-8167.2004.04422.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Sinus Recordings of Double Potentials Associated with Retrograde Conduction Through Left Atrioventricular Accessory Pathways

Abstract: In patients with connections between the paraseptal CS musculature and left atrium but no connections more laterally, retrograde left AP conduction is associated with double potentials in the CS recordings. The double potentials represent activation of the left atrial insertion of the AP (DP1) and later activation of the CS musculature (DP2) via connections between the paraseptal CS musculature and left atrium, respectively. The activation pattern of DP1 depends on AP location, thus providing important informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 15 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…We attributed DP1 and DP2 to the activation of LA and CSM, respectively, on the basis of the following observations: The morphology of DP1 is consistent with a LA "farfield" potential, while that of DP2 is consistent with the activation of the CSM (1,(3)(4)(5)(6). The LA activation earlier than a) the CSM and b) the atrium in the His-bundle region during RVA pacing suggested the presence of an AV AP, rather than a CSM-ventricular AP.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We attributed DP1 and DP2 to the activation of LA and CSM, respectively, on the basis of the following observations: The morphology of DP1 is consistent with a LA "farfield" potential, while that of DP2 is consistent with the activation of the CSM (1,(3)(4)(5)(6). The LA activation earlier than a) the CSM and b) the atrium in the His-bundle region during RVA pacing suggested the presence of an AV AP, rather than a CSM-ventricular AP.…”
Section: Discussionmentioning
confidence: 96%
“…5, the wavefront of LA (DP1) would reach the ostium of CS, and the wavefront Histological study in humans has shown that myocardial connections between LA and CSM varies greatly in size and location, and no connection or a loose connection in the distal CS is not rare (2). In contrast, the absence of LA-CSM electrical connection in the proximal CS has not ever been reported in a clinical study (3). In our previous study, double potentials were detected in 11 patients of 74 patients (14.9%) with paroxysmal supraventricular tachycardia who underwent successful ablation (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kasai et al demonstrated connections between left atrium and CS musculature using extrastimulus techniques in the human heart [5]. Akiyama et al reported double potentials associated with retrograde AP conduction caused by left atrium (the first component) and CS musculature activation (the second component) [6].…”
Section: Cs Musculaturementioning
confidence: 99%